PENGARUH PROFITABILITAS, LEVERAGE DAN LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sutina, Sutina; Yusran, Rio Rahmat (Aksara Public, 2020)
This research aimed to analyze the effect of Profitability, Leverage and Liquidity on Dividend Policy. Allegedly dominant factor can influence Dividend Policy is Profitability, Leverage and Liquidity. This research was conducted at the basic industrial and chemical manufacturing companies listed in the Indonesia Stock Exchange in 2014-2018 with a total population of 63 companies. The sampling technique used purposive sampling with a total sample of 15 companies. The data analysis technique used is multiple linear regression. The results showed that partially profitability does not have a variable effect on dividend policy, leverage and liquidity have a significant influence on dividend policy. Simultaneously, variable Profitability, Leverage and Liquidity affect the dividend policy. On testing the coefficient of determination R2, obtained variable Profitability, Leverage and Liquidity variables has a R2 value of 0.136. This means that the percentage of variables profitability, leverage and liquidity in the regression model by 13.6 percent. Or variations of variables dividend policy can be explained Profitability, Leverage and Liquidity amounted to 13.6 percent of the remaining 86.4 percent can be explained by other variables not included in this research model.